Nanoliposomal Coencapsulation of Dorema aucheri Extract and Curcumin; Enhanced Cytotoxicity, Apoptosis Induction, and Inhibition of EGFR Gene Expression in Oral Cancer Cells OCC-02 - Mahshid Azizi; Ghasem Ghalamfarsa; Fatemeh Khosravani; Hassan Bardania; Shahriar Azizi (IET Nanobiotechnology)
Curcumin is one of the natural anticancer drugs but its efficiency is limited by low stability, insufficient bioavailability, poor solubility, and poor permeability. Dorema aucheri (Bilhar) is a herb with precious pharmaceutical properties. This study aimed to develop a nanoliposome-based curcumin and Bilhar extract codelivery system. The nanocompounds were synthesized using the lipid thin-film hydration method and characterized by transmission electron microscopy, and dynamic light scattering techniques, and their cytotoxicity and apoptotic effect on the primary oral cancer cell line were evaluated via 2,5-diphenyl-2H-tetrazolium bromide assay and flow cytometry. Moreover, the expression of the epidermal growth factor receptor (EGFR) gene in the treated cells was assessed using the real-time polymerase chain reaction technique. Based on the results, nanoliposomes had a size of 91 ± 10 nm with a polydispersity index of 0.13. Free curcumin, the extract, and the curcumin-extract combination showed dose-dependent toxicity against cancer cells; yet, the extract (IC50: 86 µg/ml) and curcumin-extract (IC50: 65 µg/ml) activities were much more than curcumin (IC50: 121 µg/ml). Also, the curcumin and extract loaded on liposomes showed a dose and time-dependent cytotoxicity. After loading the curcumin-extract compound on nanoliposomes, their IC50 decreased from 180 µg/ml (within 24 hr) to 43 µg/ml (within 72 hr), indicating their sustainable release and activity. Likewise, this compound induced the highest apoptosis percentage (95%) in cancerous cells and inhibited the expression of the EGFR gene in the cells by 81% ± 3%. These findings demonstrated the effectiveness of the Bilhar extract against oral cancer cells. Also, in combination with curcumin, it showed an additive activity that considerably improved after loading on nanoliposomes.